Mango harvester reducing drudgery to growers - Srinivas, P; Singh, H S; Acharya, G C (Indian Horticulture, 2019)
Harvesting mangoes is a lot easier now. With a few modifications in the existing pole harvester, new lighter harvester is easier to use with reduced strain on shoulders and forearms. Its long soft conduit not only saves the fruits from damage due to falling on the branches and ground but also reduces chances of picking up of contaminants from the soil debris.